The Effect of Cultiving Media and N Fertilizer Application on the Growth and Results of Flowering Cabbage (Brassica oleracea var. botrytis L.) - Tarigan, Sumatera (Future Science / FSH-PH Publications, 2023)
Research to study the effect of a good combination of growing media and application of N fertilizer on the growth and yield of cauliflower (Brassica oleracea, L.). The research time was carried out from June 2022 to October 2022 at Raya Village garden, Berastagi District, Karo Regency, North Sumatra Province, with an altitude of 1,300 above sea level with latosol soil type and soil pH 6.8. This research was conducted from June 2022 to October 2022. This research was conducted with a factorial experiment of 3x2 = 6 + 1 controls arranged in a factorial randomized block design (RAK). The first factor was the composition of the planting medium (M), which consisted of 3 treatment levels, namely: Mo: Control (without mixture), M1: Soil + husk charcoal with a volume ratio (1:1), M2: Sand + charcoal husk with a volume ratio (1:1) , M3: Soil + sand + husk charcoal by volume ratio (1:1:1) . The second factor was the dose of ZA (N) fertilizer which consisted of 3 treatment levels, namely: N1 : 50 kg/ha, N2 : 100 kg/ha, N3 : 150 kg/ha . The observed variables were plant height, number of leaves, number of roots, fresh weight of plants, fresh weight of flowers/plant, dry weight of plants, initiation of flowering, flower diameter. Mixing plant media and N fertilizer can increase the growth and yield of cauliflower plants. M3N3 treatment ( Soil + sand + husk charcoal with volume ratio (1:1:1) + Nitrogen fertilizer 150 kg/ha, is the best treatment that can increase growth and yield of cauliflower on the number of roots (7.27 fruit), fresh weight of plants (7.95 g), dry weight of plants (2.69 g), initiation of flowering (6.00 hst), fresh weight of flowers/plant (6.98 g), flower diameter (3.09 mm).